Enhancing Red Brick Quality Using Corn Cob Ash and Blood Clam Shell Powder - Adisti, Najeelina Putri; Yaqub, Muhammad Ardhiansyah Sofyan; Fauziyah, Shifa; Suwarto, Fardzanela (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
Problems related to the quality of red bricks are still frequently encountered, particularly cracks or damage that occur during the firing process. To minimize these problems, efforts are needed to improve the quality of bricks through material innovation. This study aims to analyze the optimal mixture composition by substituting corn cob ash and adding blood clam shell powder to produce red bricks. Corn cob ash is used as a substitute material to reduce water absorption, with variations of 3%, 4%, and 5%, while blood clam shell powder is added at 5% to enhance compressive strength. The research method used was experimental, where the sample production process was conducted directly at the production site. A total of 21 test specimens were prepared with dimensions of 220 mm × 95 mm × 45 mm. Testing was conducted in accordance with the SNI 15-2094-2000 standard, including testing of physical properties, size, water absorption, density, and compressive strength. The research results showed that the most optimal mixture was found in variation 7, consisting of 95% clay, 5% corn cob ash, and 5% blood clam shell powder. This composition produced bricks with water absorption of 18.06%, density of 1.3 g/cm³, and average compressive strength of 42.98 kg/cm². However, this innovation requires higher production costs compared to conventional red bricks.